Our feature presentation organizational behavior - Champoux, Joseph E. (Joseph Edward) (South-Western/Thomson Learning, 2005)
Our Feature Presentation: Organizational Behavior adds excitement and relevance to Organizational Behavior topics through selected film scenes from popular film releases. This unique product combines a workbook with actual film clips on CD and Video, eliminating the need to purchase or rent costly videos. Film provides your students a visual portrayal of abstract management concepts and provides inexperienced students a greater feeling of reality and connection to the topic. Further, there are many unique aspects of film such as editing, sound, framing, and focusing techniques that make it a powerful communication device that often goes beyond what we can experience in reality. Equally powerful are the reactions of the varied responses of the viewer that can spark lively debate. Register for access to the videos online at http://featurepresentation.swlearning.com.